Disturbances of the ascending aorta biomechanics in moderate dilatation and aneurysm - A. V. Vrublevsky; D. S. Panfilov; B. N. Kozlov; V. V. Saushkin; S. I. Sazonova (Российский кардиологический журнал)
Aim. To compare disturbances of the ascending aorta (AA) biomechanics in patients with moderate dilatation and aneurysm using segmental aortic strain ultrasound.Material and methods. Fifteen patients with moderate AA dilatation (40-49 mm), 17 patients with AA aneurysm (≥50 mm) and 11 healthy volunteers (AA<40 mm) were examined using 2D multiplane transesophageal echocardiography (TEE). The entire thoracic aorta (TA) was assessed. Using 2D speckle-tracking TEE, global peak systolic circumferential strain (GCS, %), global peak systolic circumferential strain normalized to pulse pressure (GCS/PP) and aortic stiffness (β2) index at 4 TA levels (sinuses of Valsalva, sinotubular junction, mid-ascending aorta, descending aorta) were calculated.Results. In healthy volunteers with TA diameter of 26,6 mm (25,2; 28,4) unidirectional uniform GCS of 9,7% (8,4; 11,7), GCS/PP of 18,4 (14,9; 2,.6) and uniform aortic stiffness (β2) 5,9 (4,8; 6,7) in all TA segments were revealed. There was a proportionally significant decrease in deformation parameters up to negative values and an increase of the ascending aortic wall stiffness from the aortic annulus to the descending aorta with a maximum in the highest dilatation zone in patients with moderate dilatation and aneurysm. Moreover, in these patients aortic wall strain and stiffness did not differ in all TA segments (p>0,05). The AA diameter in maximum dilatation zone in patients with aneurysm was significantly higher than in patients with moderate dilatation — 52 mm (51; 55) versus 47 mm (45; 48), p<0,001, respectively. An inverse correlation between the AA diameter in maximum dilatation zone and aortic strain (GCS: r=-0,61; p<0.001 and GCS/PP: r=-0,62; p<0,001) and a direct correlation with the aortic stiffness (β2) index (r=0,56; p<0,05) were revealed.Conclusion. Assessment of the aortic biomechanics along with the AA diameter has an independent diagnostic value when choosing an individual surgical strategy in patients with moderate dilatation and AA aneurysm.